Preliminary qualitative findings: challenges in large infrastructure projects towards development of innovative performance measurement - Masrom, Md Asrul Nasid; Abd Rahim, Mohd Hilmi Izwan; Mohamed, Sulzakimin; Yunus, Riduan (Trans Tech Publications, 2015)
Performance measurement system to assess development of large infrastructure project has developed due to the unachieved of high design and technical requirements, excessive cost investments and lack of competent human resources and managerial capabilities. Growing numbers of discrepant of interest among key participants has also led to conflicts, blame cultures, and mismatches of objectives that have been found to be contributory factors to poor project performance. Although, several approaches have been determined, the challenges in terms of time, cost, and quality (objective measures) are still arguable. Further exploration requires the inclusion of additional challenges in delivering large infrastructure projects, particularly in relation to subjective measures, such as safety, relationship, satisfaction, social and environmental aspects. Owing to this limitation, preliminary findings of identifying the challenges in large infrastructure projects are vital to fulfill the current needs in the development of innovative performance measurement. The research adheres to by reviewing relevant literature and evaluating expert insights on the research topic. The results of the research would provide qualitative evidence in support of the notion that appropriate and comprehensive performance measurement to improve project outcome. This study may also encourage key stakeholders mainly involved in infrastructure projects to increase their attention on possible challenges to achieve project objectives and requirements in the development of a large project, and helps to the achievement of government transformation programme (GTP).